Who is a Confucian Today?: A Critical Reflection on the Issues Concerning Confucian Identity in Modern Times - Yao, Xinzhong (Journal of contemporary religion, 2001)
Along with the revival of Confucian values among East Asian intellectuals since the 1980s, the question of Confucian identity has been repeatedly raised. The traditional identities of Confucianism and Confucians are being challenged. A new inquiry into Confucian identity is necessary because how to define Confucianism is now taken not only as a question of how to read history, but also as an issue of how to understand current and future reality. The central concern of this paper is with the question of how the modern transformation of the tradition has fundamentally changed the parameters that used to be of importance to defining Confucian identity and with the dilemma which modern Confucians face in searching for a new identity. The paper is intended to promote a critical examination of various directions taken to re-establish Confucian identity in modern times.